An Update on the Use of Artificial Intelligence in Cardiovascular Medicine - Shiavax J. Rao; Shaikh B. Iqbal; Ameesh Isath; Hafeez Ul Hassan Virk; Zhen Wang; Benjamin S. Glicksberg; Chayakrit Krittanawong (Hearts, 2024)
Artificial intelligence, specifically advanced language models such as ChatGPT, have the potential to revolutionize various aspects of healthcare, medical education, and research. In this review, we evaluate the myriad applications of artificial intelligence in diverse healthcare domains. We discuss its potential role in clinical decision-making, exploring how it can assist physicians by providing rapid, data-driven insights for diagnosis and treatment. We review the benefits of artificial intelligence such as ChatGPT in personalized patient care, particularly in geriatric care, medication management, weight loss and nutrition, and physical activity guidance. We further delve into its potential to enhance medical research, through the analysis of large datasets, and the development of novel methodologies. In the realm of medical education, we investigate the utility of artificial intelligence as an information retrieval tool and personalized learning resource for medical students and professionals.